Contrarian anthropology : the unwritten rules of academia - Nader, Laura (Berghahn, 2018)
Analyzing the workings of boundary maintenance in the areas of anthropology, energy, gender, and law, Nader contrasts dominant trends in academia with work that pushes the boundaries of acceptable methods and theories. Although the selections illustrate the history of one anthropologist's work over half a century, the wider intent is to label a field as contrarian to reveal unwritten rules that sometimes hinder transformative thinking.